DEVELOPING THE LEARNING MODEL OF PHYSICAL EDUCATION FOR ELEMENTARY STUDENTS ON THE BASIS OF TRADITIONAL SPORT AS THE LOCAL WISDOM - Pratama, Muhammad Deswin (Sriwijaya University Learning and Education International Conference, 2018)
This study entitled “The Development of Physical Education Learning Model For Elementary School On The Basis of Traditional Sport As A Local Wisdom” aims to produce Physical Education models that valid, practical, and effective. Methods in this research is research-based development (Research-based development) or Research and Development. The results of the experiments for the validity of the small group experiments of teacher obtained the average of the answers by percentage (84%), whereas the large group trial of the prevalence rate obtained an average answer with percentage (76%), then the product has good category validity. Level of product effectiveness seen from aspect of motivation, result of small group test show relation aspect of motivation equal to 82% and large group trial is equal to 83% from motivation aspect, hence product result show level of effectiveness of good category. the development of physical education learning based of traditional sports as a local wisdom given to the learners has been effective so that it can be implemented in the application of physical education education.